أثر الحوافز على أداء العاملين في المؤسسات الإقتصادية دراسة حالة في مؤسسة سونطراك - قويدري مريم منال; شيباني حليمة; شلوفي عمير (جامعة عمار ثليجي الاغواط, 2022)
This study aims to know the extent of the impact of material and moral incentives in achieving outstanding performance among workers in the maintenance directorate institution, in the light of some variables, which are the dimensions of incentives (material incentives, moral Incentives) through the spss27 statistical analysis program to verify the effect of the independent variable on The dependent variable through the field study, the study population represented the 60 workers in the maintenance directorate institution, and the final study sample consisted of 30 workers in the institution under study, and the researcher used a questionnaire for incentives and outstanding performance of workers ،In analyzing the data contained in the questionnaires, the researcher relied on the 27spss program through the use of some statistical methods suitable for the study’s hypotheses and questions, including calculating averages and standard deviations, calculating the validity of the questionnaire..., and the study concluded that there are no fundamental difference sattributed to a variable between the variables. Personality and employee performance (gender, educational level, total years of work), the study also found that there is a statistical significance of the effect of incentives on the performance of workers, and in material incentives there is no statistically significant effect. As for moral incentives, there is a statistically significant effect at the level of morale. (0.05).